Kosakonia radicincitans and Cryptococcus laurentii controlled Penicillium expansum rot and decreased patulin production at 4 and 25 °C - Lambrese, Yesica (2021)
In the present work, we evaluated the effects of a mixture of biocontrol agents against two toxigenic strains of Penicillium expansum isolated in Argentine Patagonia from pome fruits. The two strains, INTA-5 and INTA-10, were previusly selected among ten strains coming from the Alto Valle (Rio Negro-Argentina) for their high production of patulin. For the biocontrol, Kosakonia radicincitans, Cryptococcus laurentii, and Rhodosporidium fluviale were tested in vitro experiments on Potato Dextrose Agar (PDA) dishes against the INTA-5 and INTA-10 strains. The bacterium K. radicincitans and the yeast C. laurentii were selected to be used in a mixture due to their capacity to control the fungus and reduce the mycotoxin severely. In vitro assays with the mixture showed a high antagonism against P. expansum INTA-5 and INTA-10, at 21 d of incubation at 25 °C and a patulin reduction of 98%. The mixture of microorganisms was also effective in apples stored at 25 °C for 10 d and 4 °C for 30 d. At cold storage, the mixture controlled moderately the development of rot and decreased patulin concentration. At 25 °C, the pathogen's optimal growth temperature, the mixture of Biological Control Agent (BCAs) assured both the control of rot and decrease of patulin concentration. The combination of two microorganisms, with different requirements and abilities, resulted in a mix with a strong antagonism against P. expansum with the capability to decrease the patulin concentration. Treatment with the selected mixture could be a good option for controlling strains with different behaviours and in different environmental conditions.